Non-consensual intimate image distribution: Nature, removal, and implications for the Online Safety Act - Huber, Antoinette Raffaela (European journal of criminology, 2025)
Research was conducted in partnership with the Revenge Porn Helpline (RPH) to examine the location and removal of non-consensual intimate image (NCII) abuse. By examining reports to the helpline, data were collected to uncover where intimate images were being non-consensually distributed, how they were proportionally distributed across platforms, and avenues for image removal. The data confirm that social media plays a key role in NCII distribution and provides further insight into where images are being distributed outside of social media platforms. Data on image removal indicate that knowledge of how to navigate different types of platforms is important for image removal success, making contributions from organisations such as the RPH vital, and highlighting the need to make reporting processes more accessible. The findings also indicate significant gaps within the Online Safety Act which will need to be addressed if the Act is to effectively protect victim-survivors. In particular, the need to move beyond focusing on services with the largest user numbers and broadening the scope to include smaller high-risk and problematic platforms.